Mass media influence on students' professional illusion formation - Ermakov V. A., Bozhdanova Y. V. (Interactive science, 2016)
this article presents mass media activities as a possible source of professional socialization, adequateness of social process informative display in the sphere of young people professional identity. It describes pattern distortion of occupational structure, presents the problem of mass media inadequate influence on students’ understanding about the choice and perspectives of their profession. The main factors which help to create student’s understanding about their professional future are examined.
Keywords: ценностные ориентации; средства массовой информации; искажения; общественное мнение; mass media; влияние рекламы; воздействие СМИ; моделирование поведения; поверхностное представление; иллюзии; public opinion; mass media influence; illusion; behavioral modeling; commercial influence; cotton-candy view of things; distortion; value system